Seasonal variations in methane fluxes from two tropical humic coastal lagoons densely colonized by aquatic macrophytes - Marinho, Claudio Cardoso; Fonseca, André Luiz dos Santos; Minello, Murilo; Guimaraes, Jean Remy Davee; Esteves, Francisco de Assis (Geochimica Brasiliensis, 2025)
The emission of methane (CH4) is an important factor in the Earth's climate and its excessive input into the atmosphere contributes to global warming. Natural wetlands are one of the major sources for CH4 emission to the atmosphere. This study was carried out to evaluate the seasonal variation in CH4 fluxes from two tropical coastal lagoons and the difference in the methane efflux from littoral (vegetated) and limnetic (unvegetated) regions. The study was conducted in two dry and one rainy seasons. We measured Potential Methane Fluxes (PMF), Diffusive Methane Fluxes (DMF), CH4 concentrations in the water column, rainfall, water column depth, water color, dissolved organic carbon (DOC), temperature, salinity, dissolved oxygen (DO), pH, total phosphorus (TP) and chlorophyl a (Chl-a) concentrations. The seasonality of the rainfall regime was the main factor for the seasonal changes in the PMF values, mainly through the alterations in the water column depth showing lower values during the dry period and higher values when filling occurred. The community of aquatic macrophytes contributed significantly to methanogenesis (PMF values) in the littoral region and it was possible to observe seasonal changes in CH4 dynamics in the littoral and limnetic regions.